Partial quaternization promoted metal–organic frameworks for efficient photocatalytic removal of chromium(vi). Issue 30 (28th March 2023) - Tang, Xiaocong; Wu, Xu; Wu, Hao; Zhang, Xinyu; Feng, Mingbao; Ouyang, Tong; Wang, Huanting; Ou, Ranwen
Abstract : UiO-66-NH2 is partially quaternized to produce UiO-66-N(CH3 )3 +, whose photocatalytic activity for Cr(vi ) reduction is greatly boosted by the synergy of LLCT and LMCT path. This facile and scalable one-step strategy demonstrates general applicability. Abstract : A one-step strategy is applied to partially quaternize the ligand of UiO-66-NH2, and the resultant UiO-66-N(CH3 )3 + showed greatly improved photocatalytic performance for Cr(vi ) reduction, with the apparent reaction rate constant k increasing by 8.3 times. This strategy could be used to effectively promote the performance of other MOFs-NH2, demonstrating general applicability.